Prognostic factors for uterine adenosarcoma: a review. Issue 11 (2nd November 2018) - Nathenson, Michael J.; Conley, Anthony P.
ABSTRACT: Introduction : Uterine adenosarcoma is a rare tumor with both epithelial and stromal components. Standard treatment is total abdominal hysterectomy and bilateral salpingo-oophorectomy. There is no defined role for adjuvant or neoadjuvant chemotherapy or radiation. There is a misconception that this is an indolent, low-grade sarcoma. In fact, at least 50% of patients will develop disease recurrence. Establishing prognostic factors is of paramount importance. Areas covered : This article reviews the current literature regarding adenosarcoma prognostic factors from case reports, case series, and retrospective series. An extensive review of the literature was undertaken via PubMed and Medline searches, relevant articles are included in this review. Expert commentary : The most important prognostic factors of uterine adenosarcoma are age, presence of sarcomatous overgrowth, presence of myometrial invasion, presence of lymphovascular invasion, and lymph node involvement. These factors can be used to accurately prognosticate for uterine adenosarcoma patients. Patients at low risk of disease recurrence can be identified. These patients require observation alone. Patients at high risk of disease recurrence can be identified and are candidates for aggressive therapy with adjuvant chemotherapy to reduce the risk of disease recurrence.